Effects of medium and high discomfort periods during dry environment on either pathogens causing subclinical mastitis or antimicrobial resistance of environmental Streptococci and coagulase-negative Staphylococci - Chaisri W. (2014)
The objectives of this study were firstly to compare the prevalence of subclinical mastitis among pathogens between medium and high discomfort periods of the dry season in Chiang Mai, Thailand. Secondly, as the pathogens most frequently responsible for causing mastitis in Thailand, the resistant patterns of both environmental streptococci and coagulase-negative staphylococci (CNS) were also determined for both discomfort periods. Eighty small-holder dairy farms in Chiang Mai province, Thailand, were involved in the study. All clinically-healthy cows in the enrolled farms were used and tested for subclinical mastitis. Milk samples from subclinical mastitis cows were collected for bacteriological identification. Isolates from environmental streptococci and CNS were tested for their antimicrobial susceptibility. The periods were determined by levels of discomfort from heat and humidity, including December to February as medium discomfort period (MEDIUM) and November, March and April as high discomfort periods (HIGH). From a total of 691 cows, 40.1% of cows were positive to California mastitis tests (n=277). At udder level, most pathogens found in this study were minor pathogens, especially environmental streptococci (13.0%, 138 isolates) and CNS (9.9%, 105 isolates). The prevalence of mastitis with environmental streptococci and Staphylococcus aureus in MEDIUM were more than that in HIGH (P<0.05). In contrast, Enterobacteriaceae spp. in HIGH was higher than in the Medium discomfort period (P<0.05). The majority of the environmental streptococci isolates resisted to the antimicrobial agents (97.3%). No association was found between antimicrobial resistance against environmental streptococci and dry-discomfort environmental periods. For CNS, a total of 56% of CNS isolates were resistant to one or more antimicrobial drugs. During MEDIUM discomfort period, CNS was more resistant to cloxacillin and cephalexin than during HIGH (P<0.01). In conclusion, there are some variations of pathogens causing mastitis and the antimicrobial resistant pattern of antimicrobial drugs against CNS mastitis between Medium and High discomfort periods.